Socio-cultural impacts of workplace e-learning : epistemology, ontology and pedagogy - Remtulla, Karim A., 1966- (Hershey, PA : Information Science Reference, 2010)
'This book is about using socio-culturally based research in the study of technology, learning, and workers, for the purposes of a better workplace adult education and training from workplace e-learning'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Employees -- Training of -- Computer-assisted instruction; Adult learning; Adult education -- Computer-assisted instruction; Organizational learning